Characteristics and Risk Factor of Multidrug-Resistant-Organism Infection in the Pediatric Intensive Care Unit of Dr. Kariadi Hospital Semarang - Nahwa Arkhaesi; Moh Supriatna; Yusrina Istanti; Desvita Sari; Safira Rizqi Azzahra (RSUP Dr. Kariadi, 2024)
BACKGROUND: The Pediatric Intensive Care Unit (PICU) that treats critical patients with various invasive procedures is a potential place for Multidrug Resistant Organism (MDRO) infections. This spesific unit, especially in tertiary care facilities may have higher prevalence of MDRO than non-PICU settings, causes serious disease and mortality. AIMS: To describe the characteristics and risk factor of MDRO infection in the PICU of dr. Kariadi Hospital Semarang, METHOD: Retrospective study in patients aged 1 month - 18 years with growth of germs on culture results during 2021-2022. Demographic data, use of central venous catheters and ventilator, length of stay, duration of antibiotic usage, and history of major surgery were investigated from medical records. The amount of risk expressed by the Odds Ratio (OR).RESULT: From 544 culture examinations, 199 (36.5%) germs grew, consisting of 79 MDRO isolates (39.7%) and 120 non-MDRO isolates (60.3%). Gram-negative bacteria were found in 140 samples (70.4%) with Klebsiella pneumoniae as the most common germ (15.1%) and respiratory tract infection (56.3%) being the most common infection diagnosis. As many as 24 of 30 (80%) isolates that grew Klebsiella pneumoniae were MDRO. Mechanical ventilator use (OR 2.15; 95% CI 1.07 – 4.3; p=0.043) and length of stay in the PICU (OR 2.44; 95% CI 1.21 – 4.96; p=0.018) are risk factors for MDRO infection.CONCLUSION: Klebsiella pneumoniae is the most common germ found from culture isolates and respiratory tract infection is the most common diagnosis. The use of mechanical ventilators and length of stay in the PICU are risk factors for MDRO infection.